Mutual recognition of sphingolipid molecular species in membranes - Ernst, Andreas M.; Contreras, F. Xabier; Wieland, Felix T.; Brügger, Britta (Biochimica et biophysica acta. Biomembranes, 2012)
In membranes liquid disordered (ld) and liquid ordered (lo) domains can exist that differ in fluidity and function. Lo areas are predominantly composed of cholesterol and sphingomyelin (SM). Study of the formation of such domains is hampered by a lack of methods to analyze specific lipid-lipid interactions at low concentrations of individual molecular lipid species in membranes. Here, we developed a simple biophysical method to experimentally assess the affinity of various molecular species of SM for cholesterol, and for their endogenous counterparts (kin) at physiological concentrations. Fluorescent SM (flc SM) molecular species with a conjugated pentaene system in their fatty acids are employed to monitor their affinity to either cholesterol or their kin by fluorescence unquenching. With this novel method we show that specific interactions of individual SMs with cholesterol or their kin exist, indicating the presence of SM nano‐domains in ld-phases, strictly based on kin/cholesterol recognition.